Stabilization mechanisms in discontinuous Galerkin finite element methods - Brezzi, F; Cockburn, B; Marini, L; Suli, E (2006)
In this paper we propose a new general framework for the construction and the analysis of discontinuous Galerkin (DG) methods which reveals a basic mechanism, responsible for certain distinctive stability properties of DG methods. We show that this mechanism is common to apparently unrelated stabilizations, including jump penalty, upwinding, and Hughes-Franca type residual-based stabilizations. © 2005 Elsevier B.V. All rights reserved.